A Hybrid Fuzzy-AHP and Combined Compromise Solution (CoCoSo) Approach for The Solution of Greenhouse Gas Reduction Project Selection : Study Case in Nickel Mining Company - Muttaqi, Muhamad Firdaus; Singgih, Moses Laksono (Jurnal Locus Penelitian dan Pengabdian, 2025)
This study introduces a novel decision-making approach for the nickel mining industry by integrating the hybrid fuzzy-Analytical Hierarchy Process (fuzzy-AHP) and the Combined Compromise Solution (CoCoSo) method to simultaneously evaluate and prioritize decarbonization project alternatives. This hybrid approach effectively addresses uncertainty in multi-criteria assessments while enabling balanced and rational trade-offs between competing alternatives. The research is motivated by increasing global pressure on Indonesia's nickel mining sector to adopt sustainable green mining practices, particularly by reducing greenhouse gas (GHG) emissions (CO?-eq) by approximately 29% in 2030. A leading integrated nickel mining and processing company in Indonesia is currently assessing various strategic projects to meet this decarbonization target. To support this evaluation, the fuzzy-AHP method is employed to handle the inherent uncertainty in weighting multiple criteria, while the CoCoSo method is used to rank the proposed projects based on those criteria. The evaluation covers environmental, technical, financial, and supply-related aspects. A sensitivity analysis is also conducted to test the robustness of the results against changes in the weightings of the decision criteria. The results indicate that the most influential criteria are GHG emission reduction (30.4%), system impact (26.8%), and technology feasibility (16.1%), while OPEX (9.9%), CAPEX (8.5%), and raw material supply (8.4%) are less influential. The project titled "Biomass for Kiln" is identified as the top-priority alternative, although it is highly sensitive to a decrease in the emission reduction weight and an increase in CAPEX weight. Conversely, the "Hydrotreated Vegetable Oil (HVO)" project consistently ranks the lowest in priority. These findings provide comprehensive data-driven insights to support company decision-makers in selecting the most strategic project for achieving sustainability goals.